What is changing in chronic migraine treatment? An algorithm for onabotulinumtoxinA treatment by the Italian chronic migraine group. (1st December 2020) - Sacco, Simona; Russo, Antonio; Geppetti, Pierangelo; Grazzi, Licia; Negro, Andrea; Tassorelli, Cristina; Tedeschi, Gioacchino; Martelletti, Paolo
ABSTRACT: Introduction: OnabotulinumtoxinA (OBT-A) and monoclonal antibodies (mAbs) targeting the calcitonin gene-related peptide (CGRP) pathway are two of the few treatments that ameliorate chronic migraine (CM) in randomized controlled trials and real-life studies. Separate clinical practice guidelines have been developed for the management of CM with OBT-A or CGRP-targeting mAbs. Areas covered: Considering the concomitant availability of OBT-A and CGRP-targeting mAbs as therapeutic treatment options, Italian migraine experts reviewed the evidence supporting the efficacy of OBT-A and CGRP-targeting mAbs in CM in order to rationalize the management of CM patients treated with OBT-A. Experts addressed everyday practice needs to shape the optimal pharmacological management by balancing adherence to regulatory indications, ethical considerations, and clinical expertise. Considering the remarkable challenge of improving the health and quality of life of patients with CM, even partial improvements may be clinically meaningful, particularly for those who are resistant or intolerant to oral migraine treatments. Expert opinion: In this collaborative effort, we propose a treatment algorithm that integrates the relevant aspects of managing patients with CM to provide ready-to-use practical guidance regarding the appropriate use of OBT-A.